Impact of aluminium acetate particles size on the gelation kinetics of polyacrylamide‐based gels: Rheological and molecular simulation study - Ahmed Hamza (7224470) (2023)
Inorganically crosslinked polymers have been intensively implemented for conformance control treatments in oil and gas wells at low temperatures (<90°C) because of their faster gelation time compared to organically crosslinked gels. Crosslinkers such as chromium acetate are known to be toxic, and aluminium-based alternatives have been introduced. This study aims to investigate the impact of aluminium acetate (AlAc) particle size on the gelation kinetics of polyacrylamide (PAM)-based gels at a pH of 5 and temperature of 75°C. Moreover, bentonite is used as an additive to delay the crosslinking of PAM/AlAc gels. Reducing the particle size increases the specific surface area of the particles and provides more crosslinking sites. Therefore, lower PAM concentrations (up to 5 wt.%) could be used without AlAc settling. Using 7 wt.% PAM/1 wt.% AlAc with sizes of 25 and 48 μm revealed a crosslinking time of 17 and 115 min, respectively. The addition of bentonite at low crosslinker concentrations (0.5–1 wt.%) did not decrease the gel strength of 7 wt.% PAM/1 wt.% AlAc significantly. The gelation time was extended after adding 1 wt.% bentonite to the formulation where the delay was attributed to the adsorption of AlAc on the bentonite surface that was illustrated by molecular simulation. Other Information Published in: The Canadian Journal of Chemical Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1002/cjce.24152